Transient study during clay bricks cooking in the traditional kiln; CFD numerical study - M. Ngom (Elsevier, 2021)
Traditional technologies for clay brick burning are often confronted with firing problems. The produced brick is of poor quality due to poor combustion inside the kiln. So that, cooking plays an important role because it determines the quality of the final product. Therefore, this work presents a transient computational fluid dynamic (CFD) study of firing clay bricks in the traditional oven. The heat transfer modeling in the furnace mainly is made from hydrodynamic equations and combustion reactions. Therefore, numerical simulation is done using ANSYS-Fluent software, using the standard k-ε turbulence model and the Eddy Dissipation turbulent combustion model. The results focused on the flow field, evolution of temperature, and O2 mass fraction to verify the combustion process inside the kiln. The results show that the kiln reaches the maximum temperature is in order of 900 °C and therefore verification process occurs. Moreover, the results revealed that the O2 mass fraction has the highest values at the inlet and it decreases gradually inside the kiln which gives good evidence about combustion process propagation.